Hybrid fuzzy-pid controller of an inverter for AC induction motor - Tahir Ahmed, Ahmed Mohammed (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
The usage of the AC induction motor (ACIM) becomes widely increased in the industrial applications as well as in the domestic usages, due to the good features of the ACIM and the new technologies of the electronic switching topologies. Different approaches are used to control the speed of the ACIM. One of these approaches is the Frequency variation of the sinusoidal wave form applied to the ACIM; this is achieved by using DC to AC converter (inverter). This research develops a voltage source inverter (VSI), which its output is a variable frequency sine wave between (20 and 60) Hz to control the speed of the ACIM. Proportional-integral-derivative (PID) controller will be used to improve the inverter output, while the significance of this research is the implementation of the fuzzy logic controller (FLC) as an additional controller and its rule to enhance the performance of the system. Hybrid FLC - PID controller of an inverter for ACIM is described in this research. The speed of the ACIM will be changed according to the change of the generated sine wave frequency. The output voltage error and its derivative are used as input variables for the FLC to adjust the error of the system, and FLC output will be subtracted from the output of the PID controller to reduce the error signal and eventually optimize the dynamic response of the speed controller of the motor. Simulated results show the performance of PID controller and the rule of FLC in improving the speed controller performance. Experimental results show that the variation of reference sign wave at the input can lead to variation at the output sine wave frequency; this is adequate for the variation of the motor speed. Both the VSI and FLC boards were fabricated based on programmable microcontrollers, PIC16F877A was used in the inverter circuitry to generate the pulse width modulation (PWM) and to generate internal sine wave with variable frequency to control the speed of the motor accordingly, while for the FLC circuitry it will process the rule base inference engine and calculate the FLC output upon on that. Using such a PIC controller in the inverter and FLC circuits will simplify the design, minimize the hardware and accordingly reduce the cost, at the same time it will increase the reliability of the proposed system.